Nasolabial appearance after two palatoplasty types in cleft lip and palate. (13th January 2014) - Brudnicki, A.; Bronkhorst, E. M.; Nada, R.; Dudkiewicz, Z.; Kaminek, M.; Katsaros, C.; Fudalej, P. S.
Structured Abstract Background Facial appearance is important for normal psychosocial development in children with cleft lip and palate (CLP). There is conflicting evidence on how deficient maxillary growth may affect nasolabial esthetics. Methods We retrospectively investigated nasolabial appearance in two groups, the Langenback (35 children; mean age 11.1 years; range: 7.9–13.6) and Vomerplasty (58 children; mean age 10.8 years; range: 7.8–14), who received unilateral CLP surgery by the same surgeon. The hard palate repair technique differed between the two groups. In the Langenback group, palatal bone on the non‐cleft side only was left denuded, inducing scar formation and inhibiting maxillary growth. In the Vomerplasty group, a vomerplasty with tight closure of the soft tissues on the palate was applied. Thirteen lay judges rated nasolabial esthetics on photographs using a modified Asher‐McDade's index. Results Nasolabial esthetics in both groups was comparable (p > 0.1 for each nasolabial component). Inferior view was judged as the least esthetic component and demonstrated mean scores 3.18 (SD = 0.63) and 3.13 (SD = 0.47) in the Langenback and Vomerplasty groups, respectively. Mean scores for other components were from 2.52 (SD = 0.63) to 2.81 (SD = 0.62). Regression analysis showed that vomerplasty is related with slight improvement in the nasal profile only (coefficient B = −0.287; p = 0.043; R2 = 0.096). Conclusions This study demonstrates that the use of vomerplasty instead of the Langenbeck technique is weakly associated with the nasolabial appearance among pre‐adolescent patients with UCLP.